Penerapan Metode ELECTRE Pada Sistem Pendukung Keputusan Pemilihan Asisten Laboratorium - Rini Rahayu Valentina; Volvo Sihombing; Masrizal Masrizal (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
This study aims to provide a solution to facilitate the selection of laboratory assistants at the Faculty of Technology and Computer Science, Labuhan Batu University. The solution is done by designing a decision support system (DSS) for the selection of laboratory assistants using the Electre method. This decision support system uses criteria consisting of semester grade point scores (GPS), discipline, communication, interview tests, honesty and responsibility. The alternatives used in the selection of laboratory assistants consist of 6 alternative student data. From the results of data processing using the Electre method, the Tri Erviyanti alternative with a dominant value of 1 eliminates the other 3 alternatives, so that the alternative is a student who deserves to be chosen as a laboratory assistant.